A Broken Pipeline: Effects of Gender and Racial/Ethnic Barriers on College Students' Educational Aspiration–Pursuit Gap. (August 2022) - Li, Xu; Kim, Young Hwa; Keum, Brian T. H.; Wang, Yu-Wei; Bishop, Kelley
This study examined the long-term effects of perceived educational and career barriers due to sexism and racism in college students' pursuit of postgraduate education (PE) and how such effects were different across gender and racial majority/minority groups. With a sample of 2, 717 undergraduate students, results from multinomial logistic regression showed that female and students of color not only perceived higher levels of barriers due to sexism and racism, such experiences further predicted the discrepancies between their precollege aspirations and actual pursuit for postgraduate degrees upon graduation. The higher the perceived barriers, the higher the odds of female and students of color not pursuing PE that they had aspired before college. This negative long-term effect was not observed in male students or White students. Moreover, when intersectionality was considered, women of color was the only group where perceived barriers had significant negative effects on the PE gap. Implications were discussed.